PSVII-37 Growth performance and nutrient digestibility of weaned pigs fed multi-enzyme supplemented corn-barley-soybean meal-based diets. - Park, S (J Anim Sci, 2018)
A study was conducted to determine the effects supplementing corn-barley-soybean meal-based diets for weaned pigs with a multi-enzyme on growth performance and apparent total tract digestibility (ATTD) of nutrients. Eighty-eight pigs (initial BW of 7.23 ± 1.03 kg) that had been weaned at 21 days of age and fed a drug-free nursery diet for 1 week were housed in 22 pens of 4 barrows or gilts, blocked by BW. The pigs were fed 2 experimental diets within sex, for a total of 11 pens/diet. The diets were a corn-barley-soybean meal-based diet without or with a multi-enzyme that supplied 4,000 U of xylanase, 150 U of β-glucanase and 2,500 U of protease per kilogram of diet. The basal diet contained phytase at 1,000 U/kg. The diets were fed for 5 weeks in 2 growth phases based on age; Phase 1: first 2 weeks of experiment and Phase 2: last 3 weeks of the experiment. Fresh fecal samples were collected during the last 2 days of the study to determine ATTD of nutrients. Multi-enzyme supplementation increased (P < 0.05) ADG and ADFI for Phase 1 by 27.3 and 31.3%, respectively. Multi-enzyme supplementation also tended to increase (P = 0.084) ADG for Phase 2 by 10.2%, and increased (P = 0.033) ADFI for Phase 2 by 10.5%. For the overall study, ADG and ADFI were increased (P < 0.05) by 13.8 and 13.7%, respectively. Supplementation of the basal diet with the multi-enzyme increased (P < 0.05) the ATTD of fat by 20.1%. In conclusion, the addition of multi-enzyme to phytase-supplemented corn-barley-soybean meal-based diet for weaned pigs improved their growth performance and fat digestibility, implying that the multi-enzyme product used in the current study could be added to phytase-supplemented corn-barley-soybean meal-based diet for weaned pigs to improve nutrient utilization.